E-Cigarette Use and the Risk of Myocardial Infarction in Adults: A Systematic Review and Meta-Analysis - Khairuman Fitrah Ananda Mamasta; Abigail Christine Sarumpaet; Agustina Sianturi (The Indonesian Journal of General Medicine, 2025)
Introduction: The proliferation of electronic cigarettes (e-cigarettes) has sparked a global debate regarding their cardiovascular safety, particularly their association with myocardial infarction (MI). While often perceived as a safer alternative to traditional cigarettes, their long-term effects on cardiac health are poorly understood, with existing evidence being conflicting and methodologically limited. This systematic review and meta-analysis aims to synthesize the available evidence on the relationship between e-cigarette use and the incidence of MI in adults. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar. Studies were included if they were observational (cohort, case-control, cross-sectional) or systematic reviews examining e-cigarette use in adults and reporting MI as an outcome. Data on study design, population characteristics, exposure details, and MI risk estimates were extracted. A random-effects model was used for the meta-analysis to calculate a summarized hazard ratio (HR). Results: Thirty studies were included in the systematic review. The meta-analysis of four eligible studies revealed that e-cigarette use was associated with a statistically significant increase in MI risk (HR 1.66, 95% CI 1.22–2.25, p<0.05). However, significant heterogeneity was detected (I² = 93%). Dual use of e-cigarettes and traditional cigarettes conferred the highest risk (OR up to 4.62). Compared to traditional smoking, e-cigarette use was associated with reduced odds of MI (OR 0.61). Acute use of e-cigarettes consistently increased blood pressure and heart rate. Conclusion: E-cigarette use is associated with a significantly increased risk of myocardial infarction, although the evidence is highly heterogeneous. Dual use presents the greatest danger, while switching completely from traditional cigarettes may offer a degree of harm reduction. The low certainty of the current evidence, largely from cross-sectional studies, highlights an urgent need for long-term prospective research.